Ocean current measurements with autonomous instruments - Broman, Barry (SMHI - Swedish Meteorological and Hydrological Institute, 2021)
Results from current meters: Aanderaa, Geodyne and Sensordata used in various sites depending on several projects within the oceanograhic section at SMH during 1968-1998.

NOTE: This dataset does not meet SND's nominal standards for data reusability.

Datasets are periods of use in the field with given idnames. There is a possibility to search individual datasets via an access database where the search elements are pinfo/sinfo primary/secondary info. Pinfo is similar to measurements of current, temperature and water samples all described in an pdf. Sinfo is dependant on the type of measurement giving depth and variables.

Different datasets from autonomic instruments where quality is due to how well the timestep could be found in classes 0 - 4

Data contains a large amount of unstructured information in different zips and file formats, which are difficult understand without in depth knowledge of the research area. The data is therefore provided 'as is' for anyone who is interested.

Resultat från havströmsmätare: Aanderaa, Geodyne och Sensordata som används på olika platser beroende på flera projekt inom oceanograhic delen vid SMH under 1968-1998.

OBS: Detta datasätt uppfyller inte SND: s nominella standarder för återanvändbarhet för data.

För mer information se den engelska sidan på: https://snd.gu.se/en/catalogue/study/ecds0146

Data innehåller en stor mängd ostrukturerad information i olika filformat, som inbördes inte är möjlig att orientera sig i utan ingående ämneskännedom. Data tillhandahålls därför 'as is' för den som är intresserad.
Havströmmätningar med autonoma instrument
Keywords: WIND-DRIVEN CIRCULATION; SURFACE WINDS; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav